Real-world aging and deactivation of catalytic diesel particulate filters in heavy-duty vehicles - Samuel af Ugglas; Angel Hurtado; Anders Ersson; Dawei Yao; Lars J. Pettersson; Henrik Kusar (Applied Catalysis O: Open)
Low-temperature soot oxidation in catalytic diesel particulate filters (DPF) is important for maintaining high efficiency of heavy-duty vehicles. This can be achieved by coating DPFs with an oxidation catalyst. In this work, catalytic DPFs have been collected from real-world operating heavy-duty vehicles for assessment of their catalytic activity and subsequent characterization. Testing of catalytic activity revealed the diminishing nitric oxide (NO) oxidation of the aged catalysts. The apparent reaction rates showed that the number of available catalytic sites decreased with mileage explaining the loss in activity. Characterization of the samples showed a decreasing surface area as well as an accumulation of metals and poisonous elements. An important finding from SEM-EDS analysis is the evident accumulation of phosphorus and sulfur in the washcoat in the absence of other ash-related elements, potentially explaining the decreased activity.